Urban densification, legal aspects and potential environmental impacts of cemeteries in the municipality of São Paulo, SP - Leite, Estefânia de Oliveira; Toledo, Renata Ferraz de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The objective of this articles is to verify and analyze urban density data and their correlation with the legal aspects that regulate cemeteries, in order to understand the environmental impacts that these spaces can generate. The methodological approach combines qualitative, quantitative and descriptive elements to provide a comprehensive analysis. The methodology adopted includes a case study of burial spaces in the city, exploring qualitative data and bibliographic research techniques and a documentary analysis of the relevant legislation. The results of this study allow for a deeper understanding of the complex interactions between population growth, legal regulation of cemeteries, and associated environmental impacts. The analysis sought to address the socio-environmental implications of urban cemeteries and their relationship with urban planning, public health and environmental preservation/conservation. Through an interdisciplinary approach, the expectation is for this study to expand the understanding of the importance of urban policies that consider socio-environmental impacts when planning the location and operation of cemeteries in densely populated urban areas.